Two new species of Octomeria (Pleurothallidinae) from Cordillera del Cóndor, Zamora Chichinpe, Ecuador - Vélez-Abarca, Leisberth; Jiménez, Marco M.; Baquero, Luis E. (Lankesteriana: International Journal on Orchidology, 2021)
Two new species of orchids, Octomeria pacii, and O. panguiensis are described and illustrated from Cordillera del Cóndor, Ecuador; likewise, information is provided on their distribution, habitat, and conservation status. These species differ from other species in the genus by their floral and vegetative characteristics and their apparent reproductive strategy of cleistogamy. Octomeria pacii is similar to Octomeria deceptrix, but differs in the caespitose habit, the ramicauls compressed along their entire length, the narrowly elliptical leaves, the autogamous flowers, the translucent white sepals suffused with magenta and the obovate, white lip, marked with magenta. Octomeria panguiensisis similar to O. werneri, but differs by the larger, shortly repent plants with lanceolate leaves, the cleistogamous flowers, the translucent white-colored sepals, the 5-veined lateral sepals and the oblong-trilobed lip with the apical lobe tridentate Keywords: self-compatibility, self-pollination, cleistogamy, Octomeria deceptrix, Octomeria werneri